The proud and the free : a novel - Dailey, Janet (Boston : Little, Brown, 1994)
Temple Gordon, part Scot and part native American, is raised on a southern plantation which her family loses when the Cherokees are forced westward.
Keywords: Man-woman relationships -- United States -- Fiction; Trail of Tears, 1838-1839 -- Fiction; Cherokee Indians -- Fiction; Historical fiction; United States -- History -- 1815-1861 -- Fiction; Love stories